Subgroup analysis of patients with HER2-negative metastatic breast cancer in the second-line setting from a phase 3, open-label, randomized study of eribulin mesilate versus capecitabine - Pivot, Xavier; Marmé, Frederik (Breast cancer, 2018)
This post hoc subgroup analysis of a large phase 3 study compared the efficacy and safety of eribulin versus capecitabine in patients with human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer who received second-line treatment. In the phase 3 study, women with advanced/metastatic breast cancer and ≤ 3 prior chemotherapies were randomized 1:1 to eribulin mesilate 1.4 mg/m2 intravenously on days 1 and 8, or twice-daily oral capecitabine 1.25 g/m2 on days 1-14 (21-day cycles). This analysis included 392 patients. Median overall survival was longer in patients receiving eribulin compared with capecitabine (16.1 vs 13.5 months, respectively; HR 0.77, P = 0.026). Median progression-free survival and response rates were similar between arms. Both treatments had manageable safety profiles.
Gesehen am 23.04.2020